The effect of a modified nordic curl intervention on prevalence of hamstrings injuries in a professional football team - Miller, B. (University of Manitoba, 2021)
There are many discussions about the occurrence of hamstring injury, especially in running dominant sports such as Canadian rules football. Many interventions exist to decrease the risk and/or occurrence of hamstring injury, with the Nordic Curl being among one of the most studied interventions. The Nordic Curl is commonly implemented as part of a preventative injury program, often alongside various other methods of injury prevention exercises. Limited research exists on the implementation of a "more difficult" variation of the conventional Nordic Curl, which involves keeping the concentric portion in the exercise, as opposed to only completing the eccentric portion. This modified Nordic Curl (mNC) exercise was completed in one professional football team over the duration of four competitive seasons, post practice in a progressive manner to an upper limit of 5 reps per practice. Hamstring injury data collected during the four years of implementing the mNC was compared to the prior four years of hamstring injury data in three categories: rate of hamstring injuries per 4 years; average calendar days lost due to injury; and a comparison of total hamstring injuries per timeframe of the season. Independent t-tests were calculated to analyzefor differences between rate of hamstring injuries in the two time periods (intervention vs non-intervention), and average time lost due to hamstring injury between the two time periods. Four Mann Whitney U tests were conducted to examine temporal differences in number of injuries between the intervention and non-intervention periods using four separate timeframes within the competitive season. No significant differences were found with any analyses, but large effect sizes were observed for differences between the groups for rate of hamstring injuries and the number of injuries that occurred in the first 6 weeks of the season. The results suggest the mNC does not significantly affect hamstring injury rates, time lost due to injury or specific timeframes within the competitive season. Future research should seek to investigate the modified version of the Nordic curl`s electromyographical output, as well as further study using a larger sample size than the current study.